2004
DOI: 10.2214/ajr.183.5.1831267
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Duct After Pancreatoduodenectomy: Morphologic and Functional Evaluation with Secretin-Stimulated MR Pancreatography

Abstract: The administration of secretin improves visualization of the pancreatic ducts and helps in the evaluation of remnant pancreatic function after pancreatoduodenectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
2

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 18 publications
0
27
2
Order By: Relevance
“…Secretin magnetic resonance cholangiopancreatography (sMRCP) has been used to improve the depiction of the pancreatic ducts, to qualitatively assess pancreatic exocrine function and to assess surgical anastomoses [7][8][9]. Also, sMRCP can be used to assess pancreatic duct integrity in patients post-trauma or post-acute pancreatitis [10] and to quantify pancreatic exocrine output [11].…”
Section: Introductionmentioning
confidence: 99%
“…Secretin magnetic resonance cholangiopancreatography (sMRCP) has been used to improve the depiction of the pancreatic ducts, to qualitatively assess pancreatic exocrine function and to assess surgical anastomoses [7][8][9]. Also, sMRCP can be used to assess pancreatic duct integrity in patients post-trauma or post-acute pancreatitis [10] and to quantify pancreatic exocrine output [11].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance cholangiopancreatography with secretin stimulation may be preferred because it is less invasive and provides a functional assessment of the pancreatic duct. 8 In our series, endoscopic retrograde cholangiopancreatography was attempted in 1 patient but failed because the duct could not be cannulated, suggesting a stenosis. The technique of pancreaticogastrostomy outlined in this article is technically easier than revising the existing PJ.…”
Section: Commentmentioning
confidence: 77%
“…Some clinical studies have reported that pancreatodigestive anastomotic stricture after PD induces impairment of pancreatic exocrine function [13][14][15][16] . Impairment of exocrine function derived from obstructive chronic pancreatitis is thought to be reversible to some degree.…”
Section: Discussionmentioning
confidence: 99%